401 A HUMANIZED PEGYLATED SINGLE CHAIN FRAGMENT VARIABLE (SCFV) TARGETING CARCINOEMBRYONIC ANTIGEN CELL ADHESION MOLECULE 6 REDUCES TUMOR BURDEN IN A SCID MOUSE MODEL BOTH ALONE AND IN COMBINATION WITH GEMCITABINE BY INCREASING APOPTOSIS AND DECREASING PROLIFERATION. Issue 1 (1st January 2007) - Engelhardt, K.; Cooke, L.; Riley, C.; Nagle, R.; Garewal, H.; Saldanha, J.; Mahadevan, D.
Abstract : Pancreatic ductal adenocarcinoma is the fourth leading cause of cancer and death in North America. In the year 2002, adenocarcinoma of the exocrine pancreas accounted for ≈30, 300 new ases and 29, 700 deaths. The current treatment strategy for localized pancreatic cancer is multimodality therapy combining pancreaticoduodenectomy with postoperative adjuvant chemotherapy and external beam radiation therapy, which results in a median overall survival of 12 to 24 months. For locally advanced and metastatic pancreatic cancer, the median survival is 6 to 12 months with currently available palliative chemotherapy. CEACAM6 (carcinoembryonic antigen cell adhesion molecule 6 [CD66c]) is an oncogene expressed on the cell surface as a GPI-linked glycoprotein comprised of 3 Ig-like domains capable of homophilic and heterophilic (CEACAM 5 and 8) interactions. It is highly expressed in > 90% of patients with pancreatic ductal adenocarcinoma. Deregulated expression of CEACAM6 inhibits differentiation and apoptosis of cells deprived of their anchorage to the extracellular matrix. We have previously demonstrated that CEACAM6-expressing pancreatic cancer cell lines treated with a murine monoclonal antibody (13-1) display reduced cellular viability by MTS assay, an indication of cytotoxicity. A murine scFv based on mAb (13-1) as well as a humanized form of the murine scFv also showed in vitro activity in CEACAM6-expressing cancer cell lines. In vivo studies using an SCID mouse model xenograft with BXPC-3 cells indicated a significant decrease in tumor burden as a result of treatment with a PEGylated form of the previously mentioned humanized scFv. The humanized scFv drug reduced the tumor burden as a stand-alone agent and in combination with gemcitabine compared with the control animal groups. Immunohistochemical analysis of tumors excised from animals treated with the humanized scFv and untreated animals indicated a marked increase in apoptosis (H&E) as well as a marked decrease in proliferation (Ki67) in the treated group relative to the untreated group. This observed in vivo effect on proliferation and apoptosis is currently being confirmed in vitro using CEACAM6-expressing cancer cell lines.